Smile attractiveness in patients treated with and without 4 premolar extractions: a 36 years follow up - Ros, Gabriela de Domênico Alcaraz (2023)
Introduction: The aim of this study was to assess the smile attractiveness in patients treated with or without 4 premolar extractions, a 36 years follow-up. Methods: The sample comprised 52 patients with Class I and Class II malocclusion divided into two groups. Group 1 consisted of 15 patients treated without extractions (10 females, 5 males), with the mean pretreatment (T1), posttreatment (T2) and long-term posttreatment ages (T3) of 13.2, 15.1 and 49.8 years, respectively. The mean treatment time was 1.90 years and the mean long-term follow-up was 34.7 years. Group 2 consisted of 37 patients (25 females, 12 males) treated with four premolars extractions, with mean ages at T1, T2 and T3 of 13.3, 15.7 and 53.6 years, respectively. The mean treatment time was 2.34 years and the long-term follow-up was 37.9 years. The mean retention time was 2 years in both groups. Frontal smiling photographs were obtained at the long-term follow up (T3). The evaluation of the smile attractiveness was performed with an online questionnaire where the evaluator could rate the smiling photos with a 10-point scale. The evaluators sample consisted of 62 laypeople, 33 dentists, and 89 orthodontists, randomly selected. Independent t tests, One way analysis of variance (ANOVA) and Tukey tests were used to intergroup comparisons, at p <0.05. Results: The smile attractiveness in the long-term was similar in the groups treated with 4 premolars extractions or without extractions. Women and orthodontists were more critical in assessing the smile attractiveness than men, dentists and laypeople. Conclusions: After a 36 years posttreatment the smile attractiveness was similar in patients treated with 4 premolars extractions or without extractions.